PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulansari, Putri; Ningsih, Desrini (SCIENTIA JOURNAL, 2019)
The business world resulted in the emergence of new companies so that the tight competition is inevitable that the manufacturing industry is an industry that is much cultivated by business people in Indonesia. This study entitled the influence of cash turnover, receivable turnover and inventory turnover on profitability Data analysis methods used are testing classical assumptions, multiple linear regression tests and hypothesis testing (t test and F test). The results of the t-test analysis partially indicate that cash turnover does not have a significant effect on profitability, accounts receivable turnover has a significant effect on profitability, while inventory turnover has no significant effect on profitability. The results of the F test analysis show that cashi turnoveri accountsi receivablei turnoveri andi inventoryi turnoveri doi noti havei ai significanti effecti oni profitabilityi simultaneouslyi.